ENVIRONMENT CONDUCIVE TO LEARNING OF STUDENTS IN TANGPIRUNDHAM SCHOOL UNDER THAWI WATHANA DISTRITC OFFICE, BANGKOK METROPOLITAN - Pasukree, Teerachit; Supho, Wichit; Rodmuang, Surin; Piyawanwet, Mana (Journal of MCU Nakhondhat, 2022)
The objectives of this research were to study and and to compare environment conducive to learning of students in Tangpirundham school under Thawi Watthana district office, Bangkok Metropolitan. This research was quantitative method. The population consisted of 310 students in Tangpirundham school under Thawi Watthana district office, Bangkok Metropolitan in the 2021 academic year. By using Craigsie and Morgan's sample size tables, using grade levels. then easily random a sample of 175 people were obtained and answered the questionnaire. Analyze data with statistical software packages. The statistics used in the research were content validity and questionnaire confidence. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, and One-way analysis of variance. IOC was between 0.80-1.00 and the reliability values were 0.85. The research results revealed that compare environment conducive to learning of students in Tangpirundham school as a whole was at much level. When considering each aspect , it found that building aspect , social with friend group aspect, service to leaners aspect , instructional aspect ,activity management for learners aspect, educational management aspect for respond the expectation of leaners aspect and students who different with genders and class levels showed the opinions on environment conducive to learning of students in Tangpirundham school under Thawi Watthana district office, Bangkok Metropolitan, as a whole and each aspect were not difference.